Evaluating the Effect of Audio Feedback on the Behavior of Automotive Fatigue and Distraction Detection System Users - Santos, Ricardo; Silva, Mateus; Oliveira, Ricardo R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
Vehicular fatigue and distraction detection systems are important tools to avoid traffic accidents. Furthermore, there are many related papers proposing compositions using these techniques. Nevertheless, most of the validation tests performed with these devices happen in simulated conditions or environments, without a test with actual users on a real situation. Also, few works analyze behavioral features using these systems. Inthis work, we analyze the behavioral aspects of users from afatigue and distraction detection system with and without audiofeedback. Our results indicate that this feature has a positive effect on the drivers behavior.